2000
DOI: 10.1080/10715760000300651
|View full text |Cite
|
Sign up to set email alerts
|

Reduction in free-radical-induced DNA strand breaks and base damage through fast chemical repair by flavonoids

Abstract: This paper provides evidence that dietary flavonoids can repair a range of oxidative radical damages on DNA, and thus give protection against radical-induced strand breaks and base alterations. We have irradiated dilute aqueous solutions of plasmid DNA in the absence and presence of flavonoids (F) in a "constant *OH radical scavenging environment", k of 1.5 x 10(7) s(-1) by decreasing the concentration of TRIS buffer in relation to the concentration of added flavonoids. We have shown that the flavonoids can re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
29
0
1

Year Published

2000
2000
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(33 citation statements)
references
References 64 publications
1
29
0
1
Order By: Relevance
“…Recently, it has been shown that DNA strand breaks induced by ionizing radiation were rapidly repaired by flavonoids [31]. This observation supports the notion that dietary flavonoids protect by repairing damage, as vitamin C does, rather than by direct scavenging of peroxynitrous acid.…”
supporting
confidence: 75%
“…Recently, it has been shown that DNA strand breaks induced by ionizing radiation were rapidly repaired by flavonoids [31]. This observation supports the notion that dietary flavonoids protect by repairing damage, as vitamin C does, rather than by direct scavenging of peroxynitrous acid.…”
supporting
confidence: 75%
“…Structurally important features defining the reduction potential of flavonoids are the hydroxylation pattern, a 3 ,4 -dihydroxy catechol structure in the B-ring, the planarity of the molecule and the presence of 2,3-unsaturation in conjugation with a 4-oxo function in the C-ring. Many studies have described the antioxidant efficacy of flavonoids in inhibiting the lipid peroxidation [29,82,171] and other biomolecules such as proteins and DNA [7,20,169] in vitro. Of particular importance to neurodegenerative diseases such as Parkinson's disease is the ability of flavonoids to inhibit peroxynitrite-mediated oxidation of dopamine and peroxynitrite-mediated nitration of tyrosine in vitro by a structure-dependent mechanism involving either the oxidation or nitration of the flavonoid ring system [98,150,151].…”
Section: Flavonoids: Antioxidant Propertiesmentioning
confidence: 99%
“…These data indicate that quercetin treatment may increase non-specific endonuclease activity and that sakuranetin treatment increases both non-specific and specific enzymatic activities. DNA damage (Wasson et al, 2008); (ii) donors of electron or H atom to repair some oxidative DNA damages (Anderson, Amarasinghe, Fisher, Mak, & Packer, 2000); (iii) inducers of apoptosis (Ramos, 2007); (iv) modulators of cellular proliferation (Godlewski, Slazak, Zabielski, Piastowska, & Gralak, 2006); (v) inhibitors of mutagens activation, notably by CYP450 (Hatch, Lightstone, & Colvin, 2000) and activators of phase II detoxification enzymes (Harris & Waring, 2008); (vi) modulators of cell sensibility to chemotherapy (Lambert & Yang, 2003); (vii) angiogenesis inhibitors (Kale et al, 2008); and (viii) suppressors of matrix metalloproteinases secretion and of tumor invasive behavior (Kandaswami et al, 2005). Overall the biological importance and contribution of each mechanism to the protective effect of flavonoids remain unknown and additional mechanisms are still actively investigated.…”
Section: Ex Vivo Repair Experimentsmentioning
confidence: 99%